Radiosensitivity of Rosinha and Roxinho varieties of snap beans (Phaseolus vulgaris L.) to gama radiation - Marcos Filho, Julio; Santos, Fernando Del Porto; Campos, Humberto de (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1972)
Seeds of the field bean varieties "Rosinha" and "Roxinho" (Phaseolus vulgaris L.) were subjected to gamma radiations (60Co) with the objective of studying their effect on seed germination. The radiations dosages, comprising six treatments, were: 0,0, 6,0, 12,0, 24,0, 36,0 and 48,0 krad. Seed germination was studied by means of a factorial experiment conducted under laboratory controlled conditions. The factors used were radiations dosages and eight increasing lenghts of time from date of seed irradiation. The following conclusions could be drawn from the analysis and discussion of the results obtained: a) Seed germination was adversely affected by the 12,0 krad and 24,0 krad dosages. b) No germination ocurred for the 36,0 and 48,0 krad treatments. c) The negative effect of the 6,0 krad treatment on germination was observed only sixty days after irradiations. d) Rosinha variety was more radiosensitive than Roxinho.